LEXICAL-SEMANTIC FEATURES OF PEDAGOGICAL TERMS IN ENGLISH (TAMADDUN NURI JURNALI, 2024)
we will not be mistaken if we say that pedagogical terminology is actively used in all aspects of the educational system. Much work has been done on various aspects of linguistic terminology, but at the same time the material of terms related to pedagogy is rare in linguistics.